Medicinskaâ terminologiâ v belorusskich, pol'skich, russkich i ukrainskich media: semantoko-stilističeskaâ charakteristika - Sizonov, Dimitrij Ju. (Stylistyka, 2020)
In the article, medical terminology in the modern Slavic languages is examined on the basis of mass-media resources. Based on Ukrainian, Russian, Belarussian and Polish media the stylistic functions of medical terminology and their functional role in modern informative space are analyzed. The language material gives an opportunity to explain the feature of secondary nomination of terms and also to analyze the stylistic transformations of medical terms in the Slavic mass-media texts. Special attention is paid to the semantic process of determinologization, due to which the medical terms can have different functions. It is well-proven, that media communication is a productive context for the functioning of medical terminology that envisages the achievement of the effect of predictability, influence on the recipient and designing of emotionally- expressive estimation of the information. Analyzing modern mass-media in Ukraine, the Russian Federation, the Republic of Belarus and the Republic of Poland, it is possible to make a conclusion about the prospects of media terminological transformation for the modern dynamic processes of evolution of Slavic literary languages.